Prevenção do suicídio de adolescentes na ótica dos profissionais da rede de atenção psicossocial - Nied, Camila (Universidade do Vale do Rio dos Sinos, 2021)
Suicide is recognized as a public health problem and a multidimensional phenomenon that results from the interaction of various issues inherent to life, such as social, economic, genetic, cultural, biological and environmental factors (CESCON; CAPOZOLLO; LIMA, 2018). Suicide is the deliberate act that has the intention of ending one's life and suicide attempt concerns all suicidal behavior that does not cause death. Thus, suicidal behavior involves a variety of behaviors that range from thinking about suicide (suicidal ideation), planning suicide, to the attempt and/or suicide itself (WHO, 2014). It is believed that suicide and suicide attempts are underreported data worldwide and that for each suicide there are 10 to 20 suicide attempts (MARCOLAN; SILVA, 2019; WHO, 2014). According to the World Health Organization (WHO, 2014), 800,000 people die each year by suicide and this is the second leading cause of death among young people aged 15 to 29 in the world. In relation to this, in Brazil, between 2011 and 2016, there was an increase in the number of suicides and suicide attempts among this age group, which points to the representativeness of this violence in this population (BRASIL, 2017a).
Keywords: Prevenção do suicídio de adolescentes; Atenção psicossocial; Suicídio; Tentativa de suicídio; Atenção primária à saúde; Teenage suicide prevention; Psychosocial care; Suicide; Suicide attempt; Primary health care; ACCNPQ::Ciências da Saúde::Saúde Coletiva